Maternal and umbilical cord serum‐derived exosomes enhance endothelial cell proliferation and migration. Issue 8 (23rd March 2018) - Jia, Linyan; Zhou, Xinyao; Huang, Xiaojie; Xu, Xianghong; Jia, Yuanhui; Wu, Yingting; Yao, Julei; Wu, Yanming; Wang, Kai
Abstract : We investigated the role of exosomes derived from maternal and umbilical cord blood in the regulation of angiogenesis. We report here that both maternal exosomes (MEs) and umbilical exosomes (UEs) significantly enhance HUVEC proliferation, migration, and tube formation. Importantly, ME‐treated HUVECs (MEXs) displayed significantly increased migration, but not proliferation or tube formation, compared with UE‐treated HUVECs (UEXs). We found that the expression of a subset of migration‐related microRNAs (miRNAs), including miR‐210‐3p, miR‐376c‐3p, miR‐151a‐5p, miR‐296‐5p, miR‐122‐5p, and miR‐550a‐5p, among others, were significantly increased or decreased in UEs, and this altered expression was likely correlated with the differential regulation of HUVEC migration. We also found that the mRNA expression of hepatocyte growth factor (HGF) was up‐regulated in MEXs and UEXs and, moreover, that inhibiting HGF partially abolished the enhanced cell migration induced by UEs. Our results suggest that both MEs and UEs greatly enhanced endothelial cell (EC) functions and differentially regulated EC migration, which was mostly attributed to the different expression profiles of exosomal miRNA. These findings highlight the importance of exosomes in the regulation of angiogenesis during pregnancy. Exosomal miRNAs, in particular, may be of great significance for the regulation of angiogenesis in maintaining normal pregnancy.—Jia, L., Zhou, X., Huang, X., Xu, X., Jia, Y., Wu, Y., Yao, J., Wu, Y., Wang, K. Maternal and umbilical cord serum‐derived exosomes enhance endothelial cell proliferation and migration. FASEB J . 32, 453–4543 (2018). www.fasebj.org